Ciclagem de nutrientes na sucessão milho-capim-marandu adubados com composto de lodo de esgoto: fertilidade do solo e produtividade - Kawakami, Karen Cossi [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The Brazilian Cerrado has stood out for its grain production. However, due to its condition of naturally infertile soils and the increasing price of mineral fertilizers, the search for more efficient agricultural systems and alternative fertilizers has increased significantly. The objective of this study was to evaluate the productivity and nutrient cycling in the corn-grass-marandu rotation under the residual effect of the application of sewage sludge compost (CLE) in Cerrado soil. The experiment was installed in 2017 under field conditions in Selvíria/MS, with the cultivation of rice (crop) and beans (second crop) in the agricultural years 2017/2018 and 2018/2019. In 2019/20, marandu grass (crop) and corn (second crop) were cultivated, followed again by marandu grass in 2020/21, the last two crops being studied in this research. The experimental design was adopted in randomized blocks, with four replications. The treatments were originated from a 4 x 2 + 2 factorial scheme, as follows: four doses of CLE (10; 15; 20 and 25 t ha-1, wet basis) divided into two applications, two application modes (total area and between rows of crops) and two additional treatments (without CLE application and with conventional mineral fertilization (B as boric acid, Zn as zinc sulfate, NPK 8-28-16 in corn and super simple phosphate and potassium chloride for marandu grass)). At the end of the crop cycles, soil samples (0–10 and 10–20 cm depth) were collected to assess soil fertility. Grain yield, biomass production and nutrient accumulation in marandu grass were evaluated. Corn productivity was higher with mineral fertilizer application compared to other treatments, which could not be noticed residual effect of CLE applications. For marandu grass, the two highest doses of CLE provided a higher production of dry matter at the end of the two cuts compared to the other doses. There was an increase in most nutrients accumulated in marandu grass, highlighting the two highest doses of CLE. The levels of P, B and Zn in the soil after crop cultivation increased in response to the application of CLE. It was concluded that there was nutrient cycling by the accumulation of nutrients in marandu grass and increment of nutrients in the soil. In general, the treatment fertilized with mineral fertilizer was superior to those fertilized with CLE and the application of CLE in the total area was more effective.

O Cerrado brasileiro tem se destacado pela produção de grãos. No entanto, devido a sua condição de solos naturalmente inférteis e a crescente alta dos preços dos adubos minerais, a busca por sistemas agrícolas mais eficientes e fertilizantes alternativos tem aumentado significativamente. Objetivou-se, com esse estudo, avaliar a produtividade e ciclagem de nutrientes na rotação milho-capim-marandu sob efeito residual da aplicação de composto de lodo de esgoto (CLE) em solo do Cerrado. O experimento foi instalado em 2017 em condições de campo em Selvíria/MS, com o cultivo de arroz (safra) e feijão (segunda safra) nos anos agrícolas 2017/2018 e 2018/2019. Em 2019/20, foi cultivado o capim-marandu (safra) e milho (segunda safra), seguido novamente de capim-marandu em 2020/21, sendo os dois últimos cultivos estudados nesta pesquisa. Foi adotado o delineamento experimental em blocos casualizados, com quatro repetições. Os tratamentos foram originados de esquema fatorial 4 x 2 + 2, sendo: quatro doses de CLE (10; 15; 20 e 25 t ha-1, base úmida) divididas em duas aplicações, dois modos de aplicação (área total e entrelinhas das culturas) e dois tratamentos adicionais (sem aplicação do CLE e com adubação mineral convencional (B como ácido bórico, Zn na forma de sulfato de zinco, NPK 8-28-16 no cultivo de milho e super fosfato simples e cloreto de potássio para o capim-marandu)). Ao final dos ciclos das culturas, foram coletadas amostras de terra (0–10 e 10–20 cm de profundidade) para avaliação da fertilidade do solo. Foram avaliados a produtividade de grãos, produção de biomassa e acúmulo de nutrientes no capim-marandu. A produtividade do milho foi superior com aplicação do adubo mineral comparado aos demais tratamentos, os quais não se pode notar efeito residual das aplicações do CLE. Para o capim-marandu, as duas maiores doses de CLE proporcionaram uma produção maior de matéria seca ao final dos dois cortes comparado às demais doses. Houve aumento da maior parte dos nutrientes acumulados no capim-marandu, destacando-se as duas maiores doses de CLE. Os teores de P, B e Zn no solo após o cultivo das culturas aumentaram em resposta à aplicação do CLE. Conclui-se que houve ciclagem de nutrientes pelo acúmulo de nutrientes no capim-marandu e incremento de nutrientes no solo. De modo geral, o tratamento adubado com fertilizante mineral foi superior aos adubados com CLE e a aplicação do CLE em área total mostrou-se mais efetiva.
Cycling of nutrients in the succession of corn-grass-marandu fertilized with sewer sludge compound: soil fertility and productivity
Keywords: Biossolid; Urochloa brizantha; Zea mays L.; Biossólido